Implementation of automated control of vector network analyzer and robotics arm for polarimetric ground penetrating radar imaging - Gan, Wei (2016)
As GPR is one of the best device to do near-surface studies without destructing fields [1], the underground studies turn to be more and more important in short future and a plethora of measurements and analysis is deemed to be carried out with GPR. To free manpower and increase accuracy, an automated control method integrating robots with GPR is around the corner to be developed. In this project, various areas of polarimetric GPR imaging like the features of GPR, polarimetry of SAR, HPBW of horn antenna and scattering matrix are explored. Besides, an automated control involving a SAR and a robotics arm is designed and implemented. SAR is controlled by a VNA which has been programmed in a LabView program. Different parameters can be set manually through a LabView interface. Also, the robotics arm on which antennas are mounted is programed to move along a predefined track fast and accurately. The cooperation between the VNA and the robotics arm depends on the synchronization in timeline. Both manual and automated experiments are conducted and compared. It is found that the automated experiment saves much more time and manpower than the manual method. What’ more, the results of the automated Pol-SAR experiment are far more presentable which proves the advantage of the automated control.